The renewable energy research contribution of Tanzania: A review - Shame, Buruhan Haji; Ubaidillah; Tjahjana, Dominicus Danardono Dwi Prija; Arifin, Zainal; Aziz, Muhammad; Harwijayanti, Widyanita; Haji, Mohammed M. (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2024)
The central objectives of this study are to locate existing research on renewable energy, examine the energy policy of Tanzania, assess bibliometric factors, determine the direction of the current research, and comprehend unexplored research topics. This exploration focuses on a bibliometric-based study using computer-assisted software tools known as VOS viewer and RStudio in analyzing the Scopus data retrieved package for the key phrase of